Histological and clinical evaluation of the hard palate mucous membrane graft for treatment of lower eyelid retraction. Issue 3 (20th December 2016) - Larsen, Sofie D.H.; Heegaard, Steffen; Toft, Peter B.
Abstract: Purpose: To evaluate the histological appearances of the epithelial cells and the clinical effect of the hard palate mucous membrane (HPM) graft for the treatment of lower eyelid retraction (LER). Methods: This was a follow‐up study involving 15 patients, with a total of 16 eyes operated. Five patients had LER as a result of Graves' ophthalmopathy and/or inferior rectus recession, six patients because of wearing an eye prosthesis, two patients because of previous tumour excision, one patient because of proptosis due to sphenoid wing meningioma and one patient because of previous lower eyelid blepharoplasty. Three imprint biopsies were taken from each patient, one from the tarsal conjunctiva in the healthy eye, one from the graft in the operated eye and one from unoperated hard palate. The inferior scleral show was measured on pre‐ and postoperative photographs and related to the horizontal corneal diameter. Results: Median follow‐up time was 21.2 [range 4.5–87.9] months. Imprints from the graft and the hard palate showed equally large epithelial cells; imprints from conjunctiva showed small epithelial cells. The mean (±SD) scleral show was 0.12 ± 0.09 cornea diameter before surgery and 0.0003 ± 0.08 cornea diameter at invited follow‐up (p < 0.001, paired t ‐test). Corrected for direction of gaze, the mean improvement in scleral show was 0.12 ± 0.08 cornea diameter. Thirteen of 14 patients were satisfied with the final result. Conclusion: A HPM graft for LER maintains its native epithelial morphology and gives a lasting improvement in most patients.